2015
DOI: 10.1002/anie.201500051
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient One‐Pot Four‐Segment Condensation Method for Protein Chemical Synthesis

Abstract: Successive peptide ligation using a one-pot method can improve the efficiency of protein chemical synthesis. Although one-pot three-segment ligation has enjoyed widespread application, a robust method for one-pot four-segment ligation had to date remained undeveloped. Herein we report a new one-pot multisegment peptide ligation method that can be used to condense up to four segments with operational simplicity and high efficiency. Its practicality is demonstrated by the one-pot four-segment synthesis of a plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…Finally,peptide 18 (1.2 equiv) was added to initiate the fourth NCL reaction. [13][14][15] At otal of seven steps were completed within 15 h; furthermore,t he concentration of the peptide elongated from the first peptide did not change greatly (initial, 2.1 mm ;f inal, 1.7 mm)b ecause only small amounts of additives were used for the entire synthetic procedure. The reaction product was purified by HPLC,a nd the desired peptide 19 was obtained in 59 %yield from 11,thus suggesting that each reaction step proceeded in 93 %y ield on average.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Finally,peptide 18 (1.2 equiv) was added to initiate the fourth NCL reaction. [13][14][15] At otal of seven steps were completed within 15 h; furthermore,t he concentration of the peptide elongated from the first peptide did not change greatly (initial, 2.1 mm ;f inal, 1.7 mm)b ecause only small amounts of additives were used for the entire synthetic procedure. The reaction product was purified by HPLC,a nd the desired peptide 19 was obtained in 59 %yield from 11,thus suggesting that each reaction step proceeded in 93 %y ield on average.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Unfortunately, we and others found that Thz was unstable under the hydrazide oxidation conditions, and Pentelute's group reported that an unproductive nitric oxide adduct might form . Although several N‐terminal Cys protecting groups have been reported to replace Thz, some of them are unstable to TCEP (a routine reductant in NCL), whereas others require long multistep syntheses . Luckily, we noticed that trifluoroacetyl (Tfa) protected primary or secondary amines could be mildly deprotected by treatment with aqueous base .…”
Section: Resultsmentioning
confidence: 99%
“…Two elegant studies exploited a specific cysteine protecting group strategy. 10,11 Another study relied on the differential reactivity of thiolester surrogates for setting up a kinetically controlled ligation scheme. 9 Fundamentally, the process described in Figure 4 differs from the previous studies in several aspects.…”
Section: Organic Lettersmentioning
confidence: 99%